Analisis perhitungan biaya produksi dengan metode harga pokok rata-rata tertimbang pada umkm azzawa - Hidayati, Hanny Ulfa; Maula, Kholida; Maharani, Dewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to find out the total cost of production and to find out what costs were related to the production process using the Weighted Average Cost Method for the UMKM convection of azzawa veil which occurred in May 2023. The research method used in this study was the case studies with qualitative data and quantitative data. The results of this study indicate that the total cost required by the azzawa veil convection MSME to carry out production activities in May 2023 is IDR 88,217,000.00 with a cost of production of IDR 17,050.00 per unit.